2010
DOI: 10.1016/j.tripleo.2010.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorhexidine application at longitudinal push-out bond strength of fiber posts

Abstract: After 6 months, chlorhexidine application did not effectively arrest bond strength degradation of fiber posts cemented in human roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
(41 reference statements)
1
31
1
10
Order By: Relevance
“…Chlorhexidine prevents only collagen degradation that does not interfere with polymer network stability, as demonstrated in a previous study 23 in which polymer degradation was so marked that the effect of chlorhexidine could not be verified. The polymer continues to be susceptible to water sorption and swelling; there- fore, the leaching of the polymer from the hybrid layer creates spaces and exposes the collagen fibers, which can be degraded by MMPs.…”
Section: Discussionmentioning
confidence: 77%
“…Chlorhexidine prevents only collagen degradation that does not interfere with polymer network stability, as demonstrated in a previous study 23 in which polymer degradation was so marked that the effect of chlorhexidine could not be verified. The polymer continues to be susceptible to water sorption and swelling; there- fore, the leaching of the polymer from the hybrid layer creates spaces and exposes the collagen fibers, which can be degraded by MMPs.…”
Section: Discussionmentioning
confidence: 77%
“…Leitune et al 42) recently reported to apply chlorhexidine after dentin phosphoric acid etch to evaluate the influence of chlorhexidine application at immediate and long-term bond strength of fiber post cemented to root dentin. After 6 months water aging, they found that chlorhexidine application did not effectively arrest bond strength reduction of fiber posts to root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the use of chlorhexidine pretreatment could preserve the bond strength of fiber post to radicular dentin after 12 months storage. Although there were studies on the use of chlorhexidine in etch-and-rinse adhesives 3,42,43) and there was a study to evaluate the effect of chlorhexidine application in self-etch adhesive on the immediate bond strength of resin to radicular dentin 41) , very little information is available on the application of chlorhexidine in conjunction with self-etch adhesives to improve the bond durability of resin to radicular dentin. Compared with etch-and-rinse bonding systems, self-etch bonding systems do not require rinsing after etching, and hence are more user-friendly and have lower technique sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine has the potential to inhibit matrix metalloproteinases, a group of enzymes that regulate the physiologic and pathologic metabolism of collagen-based tissues, in addition to its adsorption properties in dentinal tubules. Based on restorative dentistry studies, CHX has been shown to be beneficial to the longevity of resin restorations [6][7][8][9][10][11][12][13][14][15] . Therefore, CHX's effects on radicular dentin when using resin sealers must be studied over a long-term period.…”
Section: Endodontic Irrigants and Bond Strengthmentioning
confidence: 99%